Gradient CrN / Cr composite coating structure for nuclear fuel cladding and preparation method
By forming a gradient CrN/Cr composite coating structure on the surface of the zirconium alloy, the problems of oxidation and coating easy cracking at high temperatures are solved, and significant improvements in oxidation resistance and structural integrity are achieved.
Patent Information
- Application Number
- CN202510600641.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-12
- Publication Date
- 2025-06-10
- Estimated Expiration
- 2045-05-12
AI Technical Summary
Zirconium alloy undergoes a violent oxidation reaction with high-temperature water vapor in a reactor water loss accident, resulting in heat and hydrogen release, causing explosion, and the existing Cr coating is prone to cracking and peeling at high temperatures, reducing the protection effect.
The gradient CrN/Cr composite coating structure is adopted, including the ZrN diffusion barrier layer, the Cr gradient transition layer and the CrN/Cr multilayer structure, and is formed by ion implantation and high-power pulse magnetron sputtering technology.
Effectively inhibit Zr-Cr interdiffusion, enhance the structural integrity and oxidation resistance of the coating, improve the wear resistance and crack resistance of the coating, and significantly improve the high-temperature steam oxidation performance of zirconium alloy.
Smart Images

Figure CN120119209A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of surface treatment for coating preparation, and particularly relates to a gradient CrN / Cr composite coating structure formed by ion implantation and high-power pulsed magnetron sputtering on a Zr alloy substrate and a preparation method therefor. Background Art
[0002] At present, due to the advantages of zirconium alloys such as small thermal neutron absorption cross-section, good thermal conductivity, good irradiation stability, resistance to water-side corrosion, good mechanical properties, and easy processing, they are widely used in the field of nuclear fuel cladding for water-cooled reactors. However, under the conditions of a reactor loss-of-coolant accident, zirconium alloys will undergo a violent oxidation reaction with high-temperature steam, releasing a large amount of heat and hydrogen, triggering an explosion, resulting in a large-scale release of radioactive substances, and causing catastrophic consequences. Therefore, it is very necessary to improve the ability of the nuclear fuel cladding to resist reactor accidents, that is, to enhance its high-temperature steam oxidation resistance.
[0003] Preparing an antioxidant coating on the surface of commercial mature zirconium alloy cladding has the advantages of short R & D cycle and low cost, showing great potential for engineering applications. Metal Cr can form a relatively dense and well-protective Cr 2 O 3 film layer. At the same time, due to its good compatibility with the zirconium alloy matrix, it has become one of the preferred materials for the cladding surface coating. However, there are some problems that need to be optimized. One is that interdiffusion is likely to occur at the Zr-Cr interface. Especially in a high-temperature environment, a ZrCr 2 interdiffusion layer is easily formed in the coating-matrix interface region. ZrCr 2 is a brittle Laves phase, which has a great negative impact on the mechanical properties of the coating material. At the same time, it will also cause the loss of the Cr coating material, resulting in a reduction or even failure of the coating protection effect.
[0004] On the other hand, as a protective coating for nuclear fuel accident-tolerant cladding, there are certain requirements for the thickness, generally about 15 μm, which is a relatively thick coating for magnetron sputtering technology. The metal pure Cr coating prepared by magnetron sputtering usually shows a columnar crystal growth morphology. The continuous grain boundaries of the thick columnar crystals are a kind of defect, which is prone to cause cracking and peeling of the coating under external force. In addition, such grain boundaries are prone to allow oxygen elements to diffuse to the substrate, triggering the failure of the coating. To obtain a dense coating, if only the substrate bias voltage is increased, the internal stress of the coating will be greatly increased, and the coating is prone to adhesion failure and peeling. Summary of the Invention
[0005] To solve the above problems, the present invention provides a gradient CrN / Cr composite coating structure for nuclear fuel cladding, including: A zirconium alloy substrate; A ZrN diffusion barrier layer provided on the surface of the zirconium alloy substrate, with the thickness of the ZrN diffusion barrier layer being 50 - 200 nm; A Cr gradient transition layer located above the ZrN layer, with the total thickness of the gradient transition layer being 100 - 200 nm; A CrN / Cr multi - layer structure alternately deposited on the gradient transition layer, where the single - layer thickness of the CrN layer is 50 - 100 nm and the single - layer thickness of the Cr layer is 300 - 500 nm.
[0006] Furthermore, the Cr gradient transition layer is Cr (x-1) N x -CrN-Cr x N (1-x) transition layer, where 0 < X ≤ 1.0.
[0007] Furthermore, in the ZrN diffusion barrier layer, there is a nitrogen atom concentration gradient distribution, with the surface nitrogen content being 15 - 25 at.%, and the nitrogen content at the interface being 5 - 10 at.%.
[0008] Furthermore, in the CrN / Cr multi - layer structure, the thickness ratio of the Cr layer to the CrN layer is 4:1 to 6:1.
[0009] The present invention also provides a preparation method for the above - mentioned composite coating structure, including the following steps: Step 1: Perform ion implantation treatment on the zirconium alloy substrate, with the implanted element being N, to form a ZrN diffusion barrier layer on the surface of the zirconium alloy; Step 2: Deposit CrN with a gradient change in N content on the surface of the ZrN diffusion barrier layer by high - power pulsed magnetron sputtering to form a Cr (x-1) N x gradient transition layer; Step 3: Periodically adjust the nitrogen gas flow rate to alternately deposit the CrN layer and the Cr layer, and form a CrN / Cr multi - layer structure on the Cr (x-1) N x gradient transition layer with a gradient change in N amount.
[0010] Furthermore, in Step 1, the ion implantation energy is 50 - 100 keV, and the dose is 1×10¹ 7 -5×10¹ 7 ions / cm².
[0011] Furthermore, in Step 2, the high - pulse magnetron sputtering is carried out under the condition that the background vacuum degree ≤ 5×10 -5 Pa, and the N 2 flow rate is regulated to form a Cr (x-1) N xIntermediate layer.
[0012] Furthermore, in step 3, when depositing the CrN layer and the Cr layer, the substrate bias voltage is -50V to -150V, and the deposition temperature is 200 - 400°C.
[0013] Therefore, the beneficial effects of the present invention are as follows: effectively inhibiting the Zr-Cr interdiffusion, forming a ZrN layer on the substrate surface by ion implanting N element, and combining with the gradient design of the CrN intermediate layer to significantly slow down the interfacial interdiffusion between Zr and Cr at high temperatures. The ZrN layer can hinder the migration of Cr atoms to the substrate and avoid the generation of brittle ZrCr 2 phase. At the same time, the CrN intermediate layer further strengthens the diffusion barrier effect through chemical stability, improving the structural integrity of the coating in high-temperature environments.
[0014] Optimizing the microstructure and mechanical properties of the coating, adopting the design of periodically introducing the CrN layer (thickness 50 - 100 nm), interrupting the continuous growth of the coarse columnar crystals of the traditional Cr coating, and forming a densified structure. This method not only reduces grain boundary defects and inhibits oxygen diffusion channels, but also improves the wear resistance and crack resistance of the coating through the high hardness characteristics of CrN.
[0015] Improving the bonding strength and process stability: Cr x N-CrN-Cr x The N gradient intermediate layer realizes the compositional gradient through reactive sputtering, enhancing the bonding force between the coating and the substrate and avoiding the peeling problem caused by internal stress concentration. At the same time, the high-power pulsed magnetron sputtering technology combined with automatic control can accurately control the coating thickness and structure, ensuring the process repeatability. Brief Description of the Drawings
[0016] Figure 1 It is a surface view of the composite coating structure of the present invention.
[0017] Figure 2 It is a cross-sectional view of the composite coating structure of the present invention.
[0018] Figure 3 It is a cross-sectional view of the composite coating structure of the present invention after high-temperature steam oxidation test.
[0019] Figure 4 It is a comparison diagram after scratch test. Detailed Embodiments
[0020] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, please refer to the drawings and embodiments to further describe the present invention in detail. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Embodiment
[0021] First, a Zr-4 zirconium alloy plate with dimensions of 30×30×2 mm was selected as the substrate. After mechanical polishing to make the surface roughness Ra≤0.1 μm, it was successively subjected to ultrasonic cleaning with acetone and nitrogen drying treatment. The pretreated zirconium alloy substrate was placed in an ion implantation device, and under a vacuum of 5×10 -5 Pa, nitrogen ions with an energy of 80 keV and an implantation dose of 3×10 17 ions / cm² were implanted. The substrate temperature was controlled at 250 °C to form a ZrN diffusion barrier layer with a thickness of 100 nm on the surface, where the nitrogen atom content in the surface layer was 20.5 at.%, and the nitrogen content gradient in the interface transition region decreased to 8.2 at.%.
[0022] Subsequently, high-power pulsed magnetron sputtering (HiPIMS) was used to deposit a gradient transition layer. In a working chamber with a base vacuum of 5×10 -5 Pa, the Cr x N phase transformation was controlled by dynamically regulating the nitrogen flow rate: in the initial stage, the nitrogen flow rate was linearly increased from 0 sccm to 40 sccm, and a Cr (x-1) N x layer with a thickness of 75 nm was deposited, where 0<X≤1.0; in the second stage, the nitrogen flow rate was continuously linearly decreased from 40 sccm to 0 sccm to form a 75-nm-thick Cr x N (1-x) layer (0<X≤1.0); finally, a Cr (x-1) N x -CrN-Cr x N (1-x) gradient transition layer was formed, and the total thickness of this gradient transition layer was 150 nm.
[0023] During the alternating deposition stage, the substrate bias voltage was set to -100 V and the temperature was 300 °C. The layered growth of Cr and CrN was achieved by periodically switching the nitrogen supply. When depositing the Cr layer, nitrogen was turned off and the argon flow rate was maintained at 80 sccm, and the single-layer deposition thickness was 400 nm; when depositing the CrN layer, 40 sccm of nitrogen and 60 sccm of argon were introduced, and the single-layer thickness was controlled at 80 nm. After a total of 12 deposition cycles, a multi-layer structure with a total thickness of 5.76 μm was obtained, and the thickness ratio of Cr to CrN was strictly controlled at 5:1. Observed by transmission electron microscopy (TEM), the grain size inside the coating was uniform (30 - 50 nm), and no brittle ZrCr 2 phase was detected at the interface. The scratch test showed that the critical bonding load reached 42 N, which was 180% higher than that of the untreated zirconium alloy; after 600 seconds of high-temperature steam oxidation at 1200 °C, the oxidation weight gain was only 2.3 mg / cm², and the oxidation resistance was improved by 89%. Example
[0024] Select a tubular zirconium alloy fuel cladding (Φ10mm×0.5mm) as the substrate. After electrolytic polishing, the surface roughness Ra≤0.05μm. In the ion implantation process, a dual-energy implantation strategy is adopted: First, nitrogen ions are implanted at an energy of 50keV with a dose of 1×10¹ 7 ions / cm², and then an additional implantation of 5×10¹ 6 ions / cm² is carried out at an energy of 30keV to form a gradient ZrN layer with a thickness of about 60nm on the surface. The peak nitrogen concentration in the near-surface region reaches 18.7at.%, and the concentration gradient extends to a depth of 15μm inside the substrate.
[0025] In the magnetron sputtering deposition stage, a thinning design is achieved by optimizing the process parameters. For the transition layer, the linear increase and decrease method of nitrogen gas introduction is adopted: In the initial stage, the nitrogen gas flow rate linearly increases from 0sccm to 40sccm, and a Cr (x-1) N x layer (0<X≤1.0) with a thickness of 75nm is deposited; in the second stage, the nitrogen gas flow rate continues to linearly decrease from 40sccm to 0sccm to form a 75nm-thick Cr x N (1-x) layer (0<X≤1.0); finally, a gradient transition layer of 150nn-thick Cr (x-1) N x -CrN-Cr x N (1-x) is formed. In the alternating deposition layer, the single-layer thickness of the Cr layer is reduced to 300nm (deposition rate 18nm / min), and the single-layer thickness of the CrN layer is controlled to 60nm (deposition rate 6nm / min). After a total of 15 deposition cycles, the total thickness is 5.4μm. In particular, 0.5sccm of trace nitrogen gas is introduced in the last three depositions to increase the nitrogen content in the surface Cr phase to 3at.%, forming a surface hardening layer.
[0026] The grain size inside the coating is controlled in the range of 20-50nm. A high-temperature steam oxidation experiment is carried out at 1200℃ for 1h. Only a 3.05μm-thick Cr 2 O 3 oxide layer is formed on the coating surface, and no peeling phenomenon occurs. The additional thermal neutron absorption cross-section introduced by the coating is less than 0.1barn, meeting the operating requirements of nuclear reactors.
[0027] The technical solution of the present invention has the following advantages: 1. A breakthrough improvement in high-temperature oxidation resistance By constructing a gradient CrN / Cr composite coating structure, the present invention exhibits excellent protection capabilities under the simulated reactor loss-of-coolant accident conditions (1200 °C high-temperature steam environment). The data of Example 1 show that the oxidation weight gain of the coated sample is only 2.3 mg / cm², which is 87.6% lower than that of the uncoated zirconium alloy (18.6 mg / cm²), fundamentally suppressing the violent reaction between the zirconium alloy and high-temperature steam. This protective effect stems from the synergistic effect of the gradient transition layer: the ZrN diffusion barrier layer (50 - 200 nm) suppresses the oxygen diffusion rate to the order of 1×10⁻¹ 6 m² / s, two orders of magnitude lower than that of the traditional Cr coating; while the CrN x -CrN gradient transition layer (X = 0~1) blocks the rapid penetration path of the oxidation medium along the grain boundaries through the stepwise change of the nitrogen content. During the accident tolerance test lasting up to 600 seconds, the coating integrity retention rate reaches 98%, providing a critical time window for nuclear safety emergency response.
[0028] 2. Dual Optimization of Coating Structure Design Aiming at the failure mechanism of the zirconium alloy cladding, the present invention innovatively adopts a multi-layer composite structure design: in terms of interdiffusion inhibition, the gradient ZrN layer formed by ion implantation (surface nitrogen content 15 - 25 at.%, interface 5 - 10 at.%) makes the thickness of the Zr-Cr interdiffusion layer less than 5 nm, a 90% reduction compared to the conventional coating, effectively avoiding the formation of the brittle ZrCr 2 phase; in terms of crystal defect control, the CrN / Cr alternating deposition layer (thickness ratio 4:1 - 6:1) refines the columnar crystal size to 30 - 50 nm through periodic interface insertion, with a coating density of 99.2% and a porosity below 0.5%. This structure reduces the crack propagation rate of the coating under thermal cyclic loading to 1×10⁻ 8 m / cycle, reaching the protection level of the coating for the turbine blades of aeroengines.
[0029] 3. Synergistic Enhancement of Mechanical Properties The coating system of the present invention has achieved remarkable breakthroughs in toughening: in terms of interface bonding strength, ion implantation pretreatment has increased the critical bonding load of the coating to 42 - 45 N, which is 180% - 200% higher than that of untreated zirconium alloy (15 N), meeting the first-level requirements in the nuclear power structural material standard; in terms of toughness matching, the alternating combination of the nanocrystalline Cr layer (hardness 9 - 10 GPa) prepared by HiPIMS process and the CrN hard phase (hardness 22 - 25 GPa) makes the hardness of the composite coating reach 18 - 19 GPa (nanoindentation), and the fracture toughness KIC value reaches 4.5 MPa·m¹ / ², which is 120% higher than that of a single Cr coating; in terms of thermal shock resistance, through the regulation of the vacuum annealing process at 400 - 550 °C, the residual stress of the coating is reduced from -3.5 GPa to -1.2 GPa, and it remains intact after 2000 water quench cycles between 500 °C and room temperature, meeting the mechanical properties and thermal shock resistance of nuclear fuel assemblies under normal operating conditions.
[0030] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, and improvements made within the spirit and principle of the present invention shall be included within the protection scope of the present invention.
Claims
1. A gradient CrN / Cr composite coating structure for nuclear fuel cladding, characterized in that: include: Zirconium alloy substrate; A ZrN diffusion barrier layer is disposed on the surface of the zirconium alloy substrate, wherein the thickness of the ZrN diffusion barrier layer is 50-200 nm; A Cr gradient transition layer located on the ZrN layer, wherein the total thickness of the gradient transition layer is 100-200 nm; A CrN / Cr multilayer structure is alternately deposited on the gradient transition layer, wherein the thickness of a single CrN layer is 50-100 nm, and the thickness of a single Cr layer is 300-500 nm.
2. The gradient CrN / Cr composite coating structure for nuclear fuel cladding according to claim 1, characterized in that: The Cr gradient transition layer is Cr (x-1) N x -CrN-Cr x N (1-x) Transition layer, where 0<X≤1.
0.
3. The gradient CrN / Cr composite coating structure for nuclear fuel cladding according to claim 1, characterized in that: The nitrogen atomic concentration in the ZrN diffusion barrier layer is distributed in a gradient manner, with a nitrogen content of 15-25 at.% on the surface and 5-10 at.% at the interface.
4. The gradient CrN / Cr composite coating structure for nuclear fuel cladding according to claim 1, characterized in that: In the CrN / Cr multilayer structure, the thickness ratio of the Cr layer to the CrN layer is 4:1 to 6:
1.
5. A method for preparing a gradient CrN / Cr composite coating structure for nuclear fuel cladding according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: performing ion implantation treatment on the zirconium alloy substrate, wherein the implanted element is N, so that a ZrN diffusion barrier layer is formed on the surface of the zirconium alloy; Step 2: Plating CrN with a gradient N content on the surface of the ZrN diffusion barrier layer by high-power pulsed magnetron sputtering to form Cr (x-1) N x Gradient transition layer, where 0<X≤1.0; Step 3: Periodically adjust the nitrogen flow rate to alternately deposit CrN layers and Cr layers to form a CrN / Cr multilayer structure on the Cr gradient transition layer.
6. The preparation method according to claim 5, characterized in that: In step 1, the ion implantation energy is 50-100 keV and the dose is 1×10¹ 7 -5×10¹ 7 ions / cm².
7. The preparation method according to claim 5, characterized in that: In step 2, high power pulsed magnetron sputtering is carried out at a background vacuum of ≤5×10 -5 Under the condition of Pa, the flow rate of Ar and N2 is adjusted to maintain the working pressure at 0.5 Pa, so that Cr (x-1) N x Gradient transition layer.
8. The preparation method according to claim 5, characterized in that: In the step 3, when depositing the CrN layer and the Cr layer, the substrate bias voltage is -50V to -150V, and the deposition temperature is 200-400°C.
Citation Information
Patent Citations
Preparation method of thick CrN coating on surface of cladding material
CN109972098A
Nano twin crystal ZrN diffusion shielding layer and preparation method thereof
CN115341167A
Super-wear-resistant zirconium alloy cladding surface composite coating and preparation method thereof
CN117721417A
Cited By
Hydrogen-resistant wear-resistant coating as well as preparation method and application thereof
CN120945333A